A set of maze tests for assessing the reading comprehension of first year high school students - Vela, Reny Padre 1931- (1976)
The purpose of this study was to construct a set of maze tests for assessing the reading comprehension of First Year high school students. Forty-five first year high school students from Ramon Magsaysay (Cubao) High School took the tests and showed that the tests were relatively easy for their year level.